Analysis of Biological Asset Accounting Treatment of PT. FAP Agri Tbk - Nanik Wahyuni; Fetris Ika Firdaus Purwanti (Fakultas Ekonomi Universitas Kadiri, 2024)
This study aims to determine the application of biological asset accounting (recognition, measurement, and disclosure) at PT. FAP Agri Tbk based on PSAK 69. Data obtained using content analysis method (content analysis) on the financial statements of PT. FAP Agri Tbk in 2021. The research results show that PT. FAP Agri Tbk, although it has just been registered on the IDX, its biological accounting reporting is in accordance with PSAK 69. The company recognizes biological assets based on their type, namely Immature Plants and Mature Plants. The measurement of biological assets uses the fair value basis according to market prices that were circulating that year. Biological assets are presented in the statement of financial position section in the fixed assets and current assets sections. Companies are also required to disclose details regarding the total assets up to accumulated depreciation as a whole.